GANGGUAN BAHASA DALAM PERKEMBANGAN BICARA ANAK - Masitoh Masitoh (Universitas Muhammadiyah Kotabumi, 2019)
The problem in this article was about the language disorder in the speech development of children. The language disorder on the speech development of children were one of the type of communication disorder that indicate the children who experience the disorders process to use any symbols in language. The language disorder on speech development of children was happened cause there was a disorder on nerves system or abnormalities in related organ that related to the process to use the language and to childrens' speech which occurs due to injury or trauma when they were in prenatal, natal and postnatal. Beside that it could be also caused by the environment at the age of the development of the childrens' language and speech they were did not got a good stimulus. The childrens who experience those difficulties were late in having language development skills. This things could occur in phonology, semantics, and syntax problems so that the childrens was experience the difficulties in transformation that were highly required in communication activities. The handling goals thatcan be done for the children who had the language disorders in speech development was speech therapy, oral motor, and melody intonation.